Feasibility of Best Management Practices of Cotton as Perceived by Farmers in Nalgonda District of Telangana - Parveen, Shaik Neema; Rani, V. Sudha (Indian Journal of Extension Education, 2017)
The present investigation was carried out in Nalgonda district of Telangana with 120 cotton farmers as respondents. The  ex-post facto research design was followed in the investigation. The respondents were selected at random from four  villages of two mandals of the district. Feasibility was determined using perceived feasibility index (PFI). Seven attributes  such as suitability, profitability, complexity, observability, compatibility, cost, trialability were used to determine  perceived feasibility for each practice. The results showed that majority (66.66%) of the cotton growers perceived overall  best management practices as moderately feasible followed by highly feasible (17.5%) and less feasible (15.84%)  respectively. Practices such as spacing, intercropping, nutrient management, weed management, insect pest management,  harvest and post-harvest management were perceived as moderately feasible by majority of the farmers. Irrigation at  critical stages was perceived as highly feasible. Low perceived feasibility was observed with respect to disease  management practices.
Keywords: Feasibility; best management practices; attributes; cotton